Structural and electronic phase transitions in Sr1-xCe xMnO3 perovskites - Kennedy, B; Saines, P; Zhou, Q; Zhang, Z; Matsuda, M; Miyake, M (2008)
The structures of eight members of the series Sr1-xCe xMnO3 with 0.075≤x≤0.4 have been established using synchrotron X-ray powder diffraction. These exhibit the sequence of structures cubic/Pm3̄m x≈0.08/→ tetragonal/14/mcm x≈0.35/rarr; orthorhombic/Imma with increasing Ce content. Unusual peak broadening due to domainwall scattering is observed near the composition-induced first-order cubic-tetragonal transition. The temperature dependence of the structures for three examples x = 0.1, 0.2 and 0.35 is described. For the x = 0.1 and 0.35 samples evidence for a first-order loss of the orbital ordering associated with a cooperative Jahn-Teller distortion is presented. The onset of the orbitally disordered state is accompanied by a discontinuous reduction in cell volume. © 2008 Elsevier Inc. All rights reserved.